Management of children with functional constipation referred to tertiary care - Campos,Giovanna Roberta Camargo de (2022)
Abstract Objectives: To describe the management, to compare treatment at initial referral vs. during specialized follow-up, and to describe outcomes of children with functional constipation (FC) referred to a Brazilian tertiary care center. Methods: Retrospective study, including children (4–18 years) with FC followed at a single center from 2006 to 2019. Demographics, treatments, time of follow-up, and outcomes were analyzed. The management of FC followed an institutional protocol. Results: 104 patients were identified, 79 were eligible and included in the analysis: 59% male, mean age at referral was 6.4 years, and mean duration of symptoms was 4.4 years. There were significant changes in the therapy(ies) used at the time of referral compared to during follow-up, with a noticeable increase in the frequency of the use of polyethylene glycol, enemas, magnesium hydroxide, and bisacodyl; 5.1% received trans-anal irrigation, and 3.8% underwent surgery. Outcomes were favorable in more than half of the cases: 31% improved; 19.5% had complete resolution and 2.5% were transferred back to primary care. Symptoms remained unchanged in 30.4%, and no patients experienced worsening of symptoms. The mean duration of follow-up was 2.8 years. When comparing patients with favorable vs. unfavorable outcomes, the authors did not identify significant differences in gender, age, therapies used, duration of symptoms, or length of follow-up. Conclusions: Children with FC are often referred to specialized care not receiving optimal therapy. Many patients whose FC was labeled “refractory” may be treated successfully with a well-established plan of care, and do not truly present intractable constipation.